El valencianisme a Castelló en el segon decenni del segle XX - Joan-Rafael Ramos i Alfajarín (Caplletra: Revista Internacional de Filologia, 2015)
This paper presents an overall view of the reaffirmation of Catalan and of the orthographic and onomastic problems based on the cultural magazines which appeared in Castelló berween 1910 and 1919. The role of «La Veu de Castelló» an of Gaetà Huguet Breva's work is particularly noteworthy.